"The Kurds Have Not Made Love Their Aim": Love, Sexuality, Gender, and Drag in Ehmedê Xanî's Mem û Zîn. (November 2022) - Leezenberg, Michiel
Abstract: This paper explores the concepts and norms of gender and sexuality in Ehmedê Xanî's 17 th -century mathnawi poem Mem û Zîn, nowadays regarded as the Kurdish national epic. A reading of this poem with the aid of the conceptual tools of gender studies and the history of sexuality reveals how different its norms and concepts are not only from modern Kurdish ones, but also from those of classical Persian literature. Although the poem does not hint at any taboo concerning male love for beardless boys, it does display a remarkable asymmetry between male and female same-sex desire; it also displays distinct views of legitimate and transgressive sexuality. Thus, this poem encourages a more historicizing view of the gendered and sexual dimensions of modern (Kurdish and other) nationalism, and a greater attention for the distinct characteristics of vernacular literatures within the premodern 'Persianate cosmopolitan.'